Fatigue properties of a structural rotor blade adhesive under axial and torsional loading. Issue 3 (16th December 2022) - Kuhn, Michael; Manousides, Nikolas; Antoniou, Alexandros; Balzani, Claudio
Abstract: Axial and torsional fatigue tests at different stress ratios were performed on a structural adhesive designed for wind turbine rotor blades. By employing previously optimized specimens, fatigue properties were recorded without influences of manufacturing‐induced defects such as pores. The Stüssi S–N model was an excellent fit to the data and was combined with a Haibach extension line to account for uncertainties in the gigacycle fatigue regime. A comparison of the results with hand‐mixed specimens revealed significant and load level‐dependent differences, indicating that manufacturing safety factors should be applied to the slope of the S–N curve. The experiments were accompanied by stiffness degradation measurements, which enabled an analysis of Young's and shear modulus degradation interactions. The degradation was modeled using power law fits, which incorporated load level‐dependent fitting parameters to allow for a full description of the stiffness reduction and a prediction of the residual fatigue life of run‐out specimens. Highlights: Presented S–N curves are unaffected by manufacturing‐induced defects. Combination of Stüssi and Haibach S–N models for gigacycle fatigue approximation. Development of a load‐ and cycle‐dependent stiffness degradation model. Recommendation of a S–N slope safety factor to account for manufacturing defects.